Multiple realizations of modular flavor symmetries and their phenomenology - Carlos Arriaga-Osante; Mu-Chun Chen; Ramón Díaz-Castro; Xueqi Li; Xiang-Gan Liu; Saúl Ramos-Sánchez; Michael Ratz (Journal of High Energy Physics)
Abstract We point out that specifying the finite modular group does not uniquely fix a modular flavor symmetry. We illustrate this using the finite modular group T′. Otherwise equivalent models based on different T′ lead to modular forms with different properties and, hence, produce different phenomenological features. We exemplify this in various scenarios, and show that the ability of a given model to accommodate mass and other observed hierarchies depends sensitively on the way the T′ is implemented.